The Influence Of Trust and Social Relations On Member Loyalty At The Mangaran Branch Of BMT NU - Mufidatul Himmah; Adinda Fitri Firdaus (International Journal of Management and Business Economics, 2026)
The development of the financial industry in the era of disruption increases competition among financial institutions, making maintaining member loyalty a significant challenge for Baitul Maal wat Tamwil (BMT). This study aims to analyze the influence of trust and social relationships on the loyalty of members of BMT NU Mangaran Branch. The study used a quantitative approach with a survey method of 30 active members selected using a purposive sampling technique. Data were collected through a four-point Likert scale questionnaire and analyzed using multiple linear regression tests, t-tests, F-tests, and the coefficient of determination (R²). The results showed that trust had a positive and significant effect on member loyalty (t = 3.287; p = 0.003), as did social relationships which also had a positive and significant effect (t = 3.254; p = 0.003). Simultaneously, both variables have a significant effect on member loyalty based on the results of the F test. The coefficient of determination (R²) value of [fill in according to the research results, for example 0.68 or 68%] indicates that trust and social relationships are able to explain [68%] of the variation in member loyalty, while the rest is influenced by other factors outside the research model. This finding indicates that strengthening trust and community-based social relationships is an effective strategy to increase member loyalty while reducing their tendency to move to other financial institutions.